Akuntabilitas Direksi dalam Perseroan Terbatas Yang melakukan perbuatan melawan hukum (International Forum of Researchers and Lecturers, 2023)
This study aims to analyze the responsibilities of directors in a company through a legal approach. In this context, the responsibility of directors refers to the legal obligations attached to directors in carrying out their duties and functions in a company. This study uses the literature analysis method to collect data from various legal sources, such as laws, court decisions, and related literature. The results of the research show that the responsibility of directors in a company has a strong legal basis. The directors have an obligation to act in good faith, carry out the functions of managing the company, and protect the interests of the company and its shareholders. They must make rational decisions, based on careful consideration and adequate information. However, there are several issues that need to be considered regarding the responsibilities of directors in the company. One of them is the potential problem of law violations by the directors, whether intentional or unintentional. In this regard, there needs to be an effective oversight and accountability mechanism in place to ensure that directors are held accountable for their actions.